Taphonomy of non-biomineralized trilobite tissues preserved as calcite casts from the Ordovician Walcott-Rust Quarry, USA - Sarah R. Losso; Jennifer E. Thines; Javier Ortega-Hernández (Communications Earth & Environment, 2023)
Abstract Trilobites with appendages from the Rust Formation of New York State were discovered in the 1870s and represent one of the earliest known cases of exceptional preservation of non-biomineralized tissues. The Rust Formation trilobites feature three-dimensionally preserved walking legs and delicate respiratory lamellae, but the mechanism behind their fossilization remains unknown. Here we show that after burial, carcass decay produced framboidal pyrite, while fibrous calcite precipitated on the visceral side of the body, followed by the widespread formation of sparry calcite crystal replicating non-biomineralized morphological features. Trilobites and co-occurring calcite veins show no chemical or petrographic differences, rejecting the hypothesis that exceptional preservation was caused by a local microenvironment within enrolled trilobites. These results suggest that fine-grained sediment provided support for the appendages and facilitated their fossilization through calcite replacement. Our findings carry broader implications for understanding the exceptional three-dimensional preservation of animal Paleozoic body fossils through calcite casts.